2021
DOI: 10.1371/journal.pone.0254602
|View full text |Cite|
|
Sign up to set email alerts
|

Foliar application of seed water extract of Nigella sativa improved maize growth in cadmium-contaminated soil

Abstract: Cadmium (Cd) is a widespread heavy metal, which commonly exert negative impacts on agricultural soils and living organisms. Foliar application of seed water extract of black cumin (Nigella sativa L.) can mitigate the adverse impacts of Cd-toxicity in plants through its rich antioxidants. This study examined the role of seed water extracts of N. sativa (NSE) in mitigating the adverse impacts of Cd-toxicity on maize growth. Two maize genotypes (synthetic ‘Neelum’ and hybrid ‘P1543’) were grown under 0, 4, 8 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Kalpna and Mital [ 8 ] reported that polyphenols are natural antioxidants that act as scavengers and inhibitors of free radicals responsible for oxidative damages to both the fruits and vegetables (their primary purpose) and human body (via intake of fruit and vegetables). The plant defense mechanism is stimulated due to antioxidant expression of polyphenols [ 9 11 ]. Presence of other essential compounds such as calcium and certain beneficial nutrients like vitamins in fruit and vegetables has further been suggested to prevent osteoporosis in adults to stimulate better health and strong bones [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kalpna and Mital [ 8 ] reported that polyphenols are natural antioxidants that act as scavengers and inhibitors of free radicals responsible for oxidative damages to both the fruits and vegetables (their primary purpose) and human body (via intake of fruit and vegetables). The plant defense mechanism is stimulated due to antioxidant expression of polyphenols [ 9 11 ]. Presence of other essential compounds such as calcium and certain beneficial nutrients like vitamins in fruit and vegetables has further been suggested to prevent osteoporosis in adults to stimulate better health and strong bones [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The PLOS ONE Editors retract this article [ 1 ] because it was identified as one of a series of submissions for which we have concerns about authorship, competing interests, and peer review. We regret that the issues were not addressed prior to the article’s publication.…”
mentioning
confidence: 99%